Nanomedicine: legal and regulatory challenges in Malaysia / Muhammad Syahlan Shafie, Suriani Sulong - Shafie, Muhammad Syahlan; Sulong, Suriani (2008)
In the light of medical advancement, humanity advance rapidly in technology and every dream of a human is to live with a quality of life. Nanomedicine and nanotechnology is an advancement which not only has a potential in saving lives, but also preserves lives. In the face of that, this research is a study of legal and regulatory challenges in governing nanomedicine in Malaysia. This research looks into the issue of nanomedicine through an advantages and disadvantages of nanomedicine and nanotechnology to the human's health as well as to the environment, and the broadness of the applications of nanotechnology, along with laws governing nanomedicine in foreign countries. It is based on the qualitative methodology where in, referring to books, articles, journals as well as the Internet, to get a better insight into the topic. As a final point, it is very important to emphasis that due to its nature and novelty, nanomedicine has a lot of unknown advantages and disadvantages towards human's health quality and the environment. Therefore, this research is to propose the relevant law in Malaysia, if necessary to best fit the requirements of all aspects related to nanomedicine in Malaysian context.